Administrative aspects of parks and recreational facilities at the local government level with particular reference to the Durban municipality : a theoretical and practical perspective - Bayat, Mohamed Saheed (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2021.